2016
DOI: 10.1007/s11136-016-1320-8
|View full text |Cite
|
Sign up to set email alerts
|

The benefits of personal strengths in mental health of stressed students: A longitudinal investigation

Abstract: Individual strengths may function as a defense against perceived stress and are protective factors of mental health. These strengths maintain mental health by enhancing the psychological well-being and reducing the psychological symptoms of individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 45 publications
3
21
0
2
Order By: Relevance
“…In line with previous reports on populations experiencing stress (e.g. Martínez-Martí & Ruch, 2017;Duan, 2016;Shoshani & Slone, 2016;Weber et al, 2013), we expect transcendence strengths (such as hope, gratitude, love, spirituality, and zest), and restraint strengths (including perseverance, prudence, and self-regulation) to be the most strongly associated with psychological distress and self-efficacy. It has repeatedly been suggested that these strengths are particularly important in giving individuals the energy and determination to face challenging situations and helping them to regulate their behavior under stressful circumstances.…”
Section: The Present Studysupporting
confidence: 88%
“…In line with previous reports on populations experiencing stress (e.g. Martínez-Martí & Ruch, 2017;Duan, 2016;Shoshani & Slone, 2016;Weber et al, 2013), we expect transcendence strengths (such as hope, gratitude, love, spirituality, and zest), and restraint strengths (including perseverance, prudence, and self-regulation) to be the most strongly associated with psychological distress and self-efficacy. It has repeatedly been suggested that these strengths are particularly important in giving individuals the energy and determination to face challenging situations and helping them to regulate their behavior under stressful circumstances.…”
Section: The Present Studysupporting
confidence: 88%
“…A longitudinal study found that the students with high character strengths experience less academic-related stress throughout the semester and flourish after experiencing mild depression symptoms (Duan, 2016). Other retrospective studies revealed that character strengths can promote post-traumatic growth after traumatic events (e.g., earthquake and shooting tragedies) (Duan, Guo & Gan, 2015; Schueller et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This model emphasizes the interactions between personal characteristics and situational factors rather than objective stressors alone (Lazarus and Folkman, 1984). Cross-sectional and longitudinal studies demonstrated that individuals with positive qualities, such as caring, inquisitiveness, and self-control, often perceived limited stress and showed an improved mental well-being (Duan et al, 2015b; Duan, 2016b). Therefore, the role of positive qualities in stressful situation should be investigated.…”
Section: Introductionmentioning
confidence: 99%